Understanding Insults Across Languages: A Linguistic and Cultural Comparison of Animal-Related Idioms Among English as a Foreign Language (EFL) Students (Contrarius Series: Law & Social Justice, 2026)
Idiomatic expressions related to animals, especially insults and offensive phrases, play a significant role in reflecting cultural attitudes and shaping interpersonal communication in any language. In English and Bahasa Malaysia, such expressions are frequently used but often misunderstood in cross-cultural contexts, leading to communication breakdowns. Despite their importance, there is limited comparative research exploring the linguistic features and cultural meanings of offensive idioms in these two languages. This study addresses this gap through a mixed-methods approach, compiling a corpus of animal-related idiomatic expressions and analysing their semantic nuances. Surveys and interviews with native speakers investigate how cultural contexts influence the interpretation and use of these expressions, while focus groups explore challenges bilingual speakers face in cross-cultural communication involving offensive idioms. The findings reveal linguistic patterns and cultural influences in the respondents’ understanding of English idiomatic expressions. This research underscores the need for culturally informed language education and enhanced intercultural competence to minimize misunderstandings. By filling a critical gap in comparative linguistics, the study offers valuable insights for language teaching, translation, and fostering effective communication in multicultural settings.